2007
DOI: 10.1017/s0142716407070130
|View full text |Cite
|
Sign up to set email alerts
|

Learning prosody and fluency characteristics of second language speech: The effect of experience on child learners' acquisition of five suprasegmentals

Abstract: This study examined second language (L2) experience effects on children's acquisition of fluency-(speech rate, frequency, and duration of pausing) and prosody-based (stress timing, peak alignment) suprasegmentals. Twenty Korean children (age of arrival in the United States = 7–11 years, length of US residence = 1 vs. 11 years) and 20 age-matched English monolinguals produced six English sentences in a sentence repetition task. Acoustic analyses and listener judgments were used to determine how accurately the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
38
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 64 publications
6
38
0
Order By: Relevance
“…The result has shown that intonation patterns of beginning-level L2 English produced by Vietnamese speakers are systematically different from those of native English speakers, which can be transferred from their native tone language. Nevertheless, the advanced speakers' ability to produce native-like intonation patterns indicates the effect of language learning/experience on on F0 pattern acquisition, lending further support for the L2 prosody acquisition in previous studies (Nguyễn and Ingram, 2005;Trofimovich and Baker, 2007;Nguyễn et al, 2008). The findings of this study have an original and significant contribution to the literature because it investigated into the prosodic transfer of intonation patterns between two typologically distinct languages: English, a stress accent language and Vietnamese, a contrastive contour tone language.…”
Section: Discussionsupporting
confidence: 72%
“…The result has shown that intonation patterns of beginning-level L2 English produced by Vietnamese speakers are systematically different from those of native English speakers, which can be transferred from their native tone language. Nevertheless, the advanced speakers' ability to produce native-like intonation patterns indicates the effect of language learning/experience on on F0 pattern acquisition, lending further support for the L2 prosody acquisition in previous studies (Nguyễn and Ingram, 2005;Trofimovich and Baker, 2007;Nguyễn et al, 2008). The findings of this study have an original and significant contribution to the literature because it investigated into the prosodic transfer of intonation patterns between two typologically distinct languages: English, a stress accent language and Vietnamese, a contrastive contour tone language.…”
Section: Discussionsupporting
confidence: 72%
“…Most studies report that when learners' proficiency in a language increases, their speech rate increases, their silent pause rate decreases, and the duration of their silent pauses decreases (Cucchiarini, Van Doremalen,& Strik, 2010;Trofimovich & Baker, 2007).…”
Section: International Journal Of English Linguisticsmentioning
confidence: 99%
“…Many studies have investigated the acoustic fluency characteristics of nonnative speakers. The literature ranges from child second language (L2) learners (Trofimovich & Baker, 2007) to very advanced L2 speakers (Riazantseva, 2001). Nonnative speech is reported to contain more disfluencies than native speech (e.g., Cucchiarini, Strik, & Boves, 2000) and nonnative speakers are seen to become more fluent as their proficiency in the nonnative language advances (e.g., Freed, 2000;Towell, Hawkins, & Bazergui, 1996).…”
Section: Native and Nonnative Fluencymentioning
confidence: 99%